2015
DOI: 10.1371/journal.pone.0144540
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the DNA Damage Response and KMT2A Rearrangement in Fetal Liver Hematopoietic Cells

Abstract: Etoposide, a topoisomerase 2 (TOP2) inhibitor, is associated with the development of KMT2A (MLL)-rearranged infant leukemia. An epidemiological study suggested that in utero exposure to TOP2 inhibitors may be involved in generation of KMT2A (MLL) rearrangement. The present study examined the mechanism underlying the development of KMT2A (MLL)-rearranged infant leukemia in response to in utero exposure to etoposide in a mouse model. Fetal liver hematopoietic stem cells were more susceptible to etoposide than ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Epidemiological and genetic studies support the contention that the in utero origin of MA4 in infant B-ALL may be the result of transplacental exposures during pregnancy to quinone-based chemicals or dietary flavonoids [ 3 – 5 ]. This parallels the origin of therapy-related “secondary” leukemias harboring MLL - rearrangements [ 4 , 6 , 7 ] and is supported by the finding that MLL gene rearrangements can be induced in vitro and in vivo in hematopoietic stem/progenitor cells (HSPCs) at different ontogeny stages by etoposide, a topoisomerase-II inhibitor commonly used in chemotherapy regimens [ 8 11 ].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Epidemiological and genetic studies support the contention that the in utero origin of MA4 in infant B-ALL may be the result of transplacental exposures during pregnancy to quinone-based chemicals or dietary flavonoids [ 3 – 5 ]. This parallels the origin of therapy-related “secondary” leukemias harboring MLL - rearrangements [ 4 , 6 , 7 ] and is supported by the finding that MLL gene rearrangements can be induced in vitro and in vivo in hematopoietic stem/progenitor cells (HSPCs) at different ontogeny stages by etoposide, a topoisomerase-II inhibitor commonly used in chemotherapy regimens [ 8 11 ].…”
Section: Introductionmentioning
confidence: 81%
“…A recent in vivo study has reported that rearrangements of the MLL gene can only occur when cooperating defects in the DDR are in place. For instance, defective ATM, CHK2 and p53 signaling bypasses arrest of cells in G2/M phase, thus limiting the time for the cells to repair the damage before continuing to divide [ 11 , 32 ]. Because syngeneic cell lines were used it cannot be rule out that parallel or downstream insults cooperating with MLL fusions are also required to render further DNA damage vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Also, murine studies point to the life stage-related susceptibility with regard to topo II poisoning. Nanya et al (2015) demonstrated that mouse foetal liver HSPCs were more susceptible to etoposide than maternal bone marrow mononuclear cells.…”
Section: Modifying Conditions During the Embryo-foetal Periodmentioning
confidence: 99%
“…The MLL gene encodes a methyltransferase with activity for lysine 4 of histone H3 (H3K4), which mediates changes in chromatin associated with epigenetic transcriptional activation that plays an essential role in regulating gene expression during early development and hematopoiesis [ 66 ]. Rearrangements involving the MLL gene have been reported to occur only in mice with defects in DNA damage response and not in wild-type animals [ 67 ]. MLL -r functions as the initiating, and perhaps the sole driving, oncogenic event by dysregulating epigenetic and/or transcriptional programs [ 33 ] ( Figure 1 ).…”
Section: Pathobiology Of Pediatric Leukemiasmentioning
confidence: 99%
“…, benzoquinone), quinolone antibiotics, bioflavonoids present in some fruits and vegetables and some pesticides [ 7 , 33 , 68 ]. However, exposure to topoisomerase-II inhibitors is not sufficient per se for rearrangement of MLL , and the genetic background, such as mutations in the DNA damage response pathway, may influence the likelihood of MLL -r [ 67 ].…”
Section: Pathobiology Of Pediatric Leukemiasmentioning
confidence: 99%